(3QSGdI JhHjN GdNGFH GdYGLR Scjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUd cJGH GdTjN GdaGVd hGdLeGYI KHJge Gddg Ydi WGYI hdi GdOjf hbQCJg hageJg hJYLHJ ef ELJeGYce s
(3BNQgG (B:s
(3hbO CYPQ ef CfPQ hCfJe ai CfaSce eNjQhf (B_ (3heG Ydi GdQShd GdfGUM Shi GdHdGZ GdeHjf hGdMeO ddg hMOg hHg GSJYjf Je JhHjN GdNGFH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis